Osteopontin expression in reactive lesions of gingiva - ELANAGAI,Rathinam (2015)
Reactive proliferations of the gingiva comprise lesions such as pyogenic granuloma (PG), inflammatory fibroepithelial hyperplasia (IFH), peripheral ossifying fibroma (POF), and peripheral giant cell lesion. Osteopontin (OPN) has a dual role, it promotes mineralization when it is bound to solid substrate, and on the other hand, it inhibits mineralization when it is seen in association with solution. Objectives The study aimed to evaluate the expression of osteopontin in normal gingival tissue and different types of focal reactive proliferations of gingival tissue, and its role in the development of calcification within it. Material and Methods The presence and distribution of osteopontin was assessed using immunohistochemistry in five cases of normal gingival tissue and 30 cases of focal reactive proliferations of gingiva. Results There was no expression of osteopontin in normal subjects. Few cases of pyogenic granuloma, inflammatory fibroepithelial hyperplasia, and all the cases of peripheral ossifying fibroma showed positivity for osteopontin in the inflammatory cells, stromal cells, extracellular matrix, and in the calcifications. Conclusion The expression of osteopontin in all the cases of peripheral ossifying fibroma speculates that the majority of the cases of peripheral ossifying fibroma originate from the periodontal ligament cells. The treatment modalities for peripheral ossifying fibroma should differ from other focal reactive proliferations of gingiva.